The Sustainability of Japan’s Government Debt: A Review - Miyazaki, Tomomi; Onji, Kazuki (Scientific Research, 2017)
This paper reviews the literature on the sustainability of Japanese government debt/deficit. First, we offer an overview of the approaches and the key findings on the sustainability analysis. Second, we introduce the arguments of Hoshi and Ito [1], which they predict that foreign investors’ share of JGBs could exceed beyond domestic ownership. Finally, we discuss the coordination problem in the JGB market based on the findings of Onji et al. [2] that examine how government withdrawal from the JGBs could roil the market.
Keywords: Sustainability of Government Deficit; Deficit Gamble; Tipping Point of “Crisis"; Home Bias; Coordination Problem